Identification of RNA-binding protein hnRNP C targeting the 3’UTR of the TAP-associated glycoprotein tapasin in melanoma - Yuan Wang; Barbara Seliger (OncoImmunology)
Deregulation or loss of the human leukocyte antigen class I (HLA-I) molecules on tumor cells leading to inhibition of CD8+ T cell recognition is an important tumor immune escape strategy, which could be caused by a posttranscriptional control of molecules in the HLA-I pathway mediated by RNA-binding proteins (RBPs). So far, there exists only limited information about the interaction of RBPs with HLA-I-associated molecules, but own work demonstrated a binding of the heterogeneous ribonucleoprotein C (hnRNP C) to the 3’ untranslated region (UTR) of the TAP-associated glycoprotein tapasin (tpn). In this study, in silico analysis of pan-cancer TCGA datasets revealed that hnRNP C is higher expressed in tumor specimens compared to corresponding normal tissues, which is negatively correlated to tpn expression, T cell infiltration and the overall survival of tumor patients. Functional analysis demonstrated an upregulation of tpn expression upon siRNA-mediated downregulation of hnRNP C, which is accompanied by an increased HLA-I surface expression. Thus, hnRNP C has been identified to target tpn and its inhibition could improve the HLA-I surface expression on melanoma cells suggesting its use as a possible biomarker for T-cell-based tumor immunotherapies.